An investigation of the heat transfer coefficient during refrigerant evaporation - Dutkowski, Krzysztof; Kruzel, Marcin; Bohdal, Tadeusz (Instal, 2023)
This study presents the experimental research data on the local heat transfer coefficient during refrigerant expansion evaporation in horizontal pipe minichannel. Heat exchange took place between the heated channel wall and the working fluid flowing inside (R134a and R404A). AISI 316 stainless steel pipe minichannels with an internal diameter in the range of di = 0.64 – 2.30 mm were used. The so-called minichannels are widely used to build miniature heat exchangers. Tests carried out in the range of mass flux density G = 350 – 1400 kg/(m2s) and heat flux density reaching q = 90 kW/m2 allowed to observe the occurrence of the flashing phenomenon, not observed in conventional channels. It has been shown that in the zone covered by the flashing phenomenon, the heat exchange conditions deteriorate, and the value of the local heat transfer coefficient in this zone may drop by up to 50%.